Optimization on the Ultra-low NOx Emission Uniformity and Analysis on the Safety Strategy of SCR Denitration System - Litao QU; Chao LI; Dexin WANG; Honghai YU; Jia DU; Xiaohui QI (Zhongguo dianli)
In order to keep the NOx emission concentration and ammonia escape volume within a controllable and stable range after the transformation of ultra-low emission of the SCR reactor, by taking the SCR denitrification system of a 600 MW coal-fired unit as the research object in the case studies, the inconsistency between the data of on-line monitoring (CEMS) measurement acquired from SCR reactor outlet and total discharge outlet is analyzed and investigated in this paper. Through the measurement and testing on the flow distribution at both the entrance and exit of SCR reactor, as well as the concentration field of NOx and NH3 with the structural characteristics of SCR denitrification system taken into account, the causes of the problems are explored, then the corresponding optimization and tuning scheme are formulated and the effectiveness of the scheme is verified. The results show that the heterogeneity of the molar ratio of ammonia to nitrogen at the inlet of SCR reactor is the main reason for the uneven distribution of NOx concentration at the outlet of SCR reactor. Through the optimization and tuning processes, the homogeneity of NOx concentration distribution at the outlet of SCR reactor is effectively improved, and the ammonia escape volume is reduced as well. The measurement data of the NOx emission concentration acquired by CEMS from SCR reactor outlet are basically consistent with the total discharge from the outlet of chimney. Meanwhile, based on the curve representing the relationship between NH3 and NOx concentration at the outlet of reactor SCR obtained by repeated experiments, this paper proposes both the minimum concentration for safety control and the optimal concentration of NOx safety-control, so as to facilitate the operation and control of SCR denitrification system in the later stage.